A review of the impact of noise on dogs between 2018 and 2023 - Rojas, Jhakelyne (2024)
Called man's best friend, but we do not realize the damage caused by what we call sound for them is noise, they have a sensitivity in the ears so extreme as they are able to perceive with higher frequencies, which is why the objective was to determine the impacts of noise in dogs. The methodology used for the systematization of the information was the PRISMA 2020 statement, to determine the annual growth of the scientific production was calculated with the digital tool Calcuvio and the data analysis was performed with Microsoft Office Excel version 2016 and VOSviewer version 1.6.19. The geographical distribution of research by year was focused on 2018 and 2022, the pioneer country with the highest publication was the United States, the scientific production was 30.26% (low growth), the keywords with the highest number of co-occurrences were "stress" and "noise" and "dog" and the most frequent impacts of noise in dogs were on behavioral changes and fear-anxiety. It is concluded that for future research, noise preventive measures should be sought and the degree of affection in dogs should be evaluated.